EFEK KOMBINASI KLOROKUIN DAN N-ACETYL CYSTEINETERHADAP JUMLAH TROMBOSIT MENCIT GALUR BALB/C YANG DIINFEKSI Plasmodium berghei - Mulyastuti, Yuanita; Widijanti, Anik; Ali, Mulyohadi; Iskandar, Agustin; Fitri, Loeki Enggar (Fakultas Kedokteran Universitas Brawijaya, 2004)
Malaria is the most important of the parasitic diseases of humans. In Indonesia, about more than 70 million people live in area which is endemic to malaria, about 15 million new case ofmalaria occurred every year. In malaria immune response forms free radical which assist to eliminate the cause of disease but also destroys endothelial cells at various organ. This oxidative damage plays an important role in the development of malarial thrombocytopenia. The aim of this research was to investigate the effect of Choroquine combine with N-Acetyl cysteine on the degree of parasitemia and platelets amount during malaria infection. Combination of Chloroquine and N-Acetyl cysteine have been tested by using experimental research method in male Balb/c mice which was infected by Plasmodium berghei. Measurement of the degree ofparasitemia was done everyday and the amount of the platelet as one of the nonspecific cellular immunity parameter at malaria was calculated once in three days. Treatment group were divided to eight groups, group of chloroquine(0,05 mg/gr), group of N-Acetylcysteine with dose 0,25 mg/gr, 0,5 mg/gr, and 1 mg/gr and also combination group of chloroquine and N-Acetyl cysteine with constant dose of chloroquine(0,05 mg/gr) and various dose of N-Acetyl cysteine(0,25 mg/gr, 0,5 mg/gr, and 1 mg/gr). One group consistedof infected mice without treatment as control group.